2001
DOI: 10.1152/ajplung.2001.281.5.l1106
|View full text |Cite
|
Sign up to set email alerts
|

Genes other than TLR4 are involved in the response to inhaled LPS

Abstract: For several decades, the mouse strains C3H/HeJ and C57BL/10ScNCr have been known to be hyporesponsive to endotoxin or lipopolysaccharide (LPS). Recently, mutations in Toll-like receptor (TLR) 4 have been shown to underlie this aberrant response to LPS. To further determine the relationship between TLR4 and responsiveness to LPS, we genotyped 18 strains of mice for TLR4 and evaluated the physiological and biological responses of these strains to inhaled LPS. Of the 18 strains tested, 6 were wild type for TLR4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 23 publications
2
60
2
Order By: Relevance
“…In addition, the LPS in the OVA exposures may have been responsible for increase of neutrophils present. All the mouse strains that had increased neutrophilia in our study have been found to respond to aerosolized LPS (29). Furthermore, the C3H/HeJ strain, which is unresponsive to LPS (29), did not have increased neutrophilia after OVA sensitization and challenge.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the LPS in the OVA exposures may have been responsible for increase of neutrophils present. All the mouse strains that had increased neutrophilia in our study have been found to respond to aerosolized LPS (29). Furthermore, the C3H/HeJ strain, which is unresponsive to LPS (29), did not have increased neutrophilia after OVA sensitization and challenge.…”
Section: Discussionmentioning
confidence: 53%
“…In general, inhalation or nasal aspiration of endotoxin by mice induces similar host responses and changes (35,39), and these reflect human airway responsiveness (33).…”
Section: Discussionmentioning
confidence: 99%
“…The coupled role for TLR4 and induction of iNOS has been indicated in different organs, such as a TLR4-triggered iNOS expression and hyperpermeability in response to ozone exposure in the lungs (Jones et al 2001, Kleeberger et al 2001, and a correlated TLR4 expression with iNOS/NO actions in the myocardium during heart failure (Frantz et al 1999). Furthermore, among macrophages the LPS-induced iNOS response is significantly higher in those that express high numbers of TLR4 (Dil and Qureshi 2002).…”
Section: Alterations In Nnos By MD Cells As Part Of Compensatory Intementioning
confidence: 99%